Banking awareness of the Algerian individual: a survey study on the reasons of non-adoption and ways to activate - Benbouzid, Sliman (Finance and Business Economies Review, 2022)
This research came to answer the problem related to identifying the most important reasons for not adopting the banking awareness of the Algerian individual, and what are the most important means of activation? By doing a survey on a sample of individuals according to the questionnaire method, so that the social networking site (Facebook) was relied upon to distribute the search tool in a snowball random sampling method, and data was analyzed through statistical tests (Normality test, Mann Whitney test, Kruskal Wallis test( This research concluded that there is a great consensus about the reasons for not adopting banking awareness and ways to activate it according to the viewpoint of the members of the studied sample, and the demographic characteristics of the studied sample, especially the nature of income, previous dealings with the bank, educational level and experience have a strong impact on the answers, which reflects the ability of individuals to understand the nature and privacy of banking activity in general, and how to benefit from the services provided by banks in particular, thus enhancing banking awareness